Crime, insecurity, and community policing: experiments on building trust - Blair, Graeme; Christia, Fotini; Weinstein, Jeremy M. (Cambridge studies in comparative politics, 2024)
"Presenting the outcome of a major research initiative involving two dozen scholars around the world, this book offers rigorous evidence of the efficacy of community policing in reducing crime and increasing trust in a diversity of political contexts"--